A Prioritized Inventory of Crop Wild Relatives and Wild Harvested Plants of Italy. Issue 4 (1st July 2014) - Landucci, Flavia; Panella, Lorenzo; Lucarini, Domenico; Gigante, Daniela; Donnini, Domizia; Kell, Shelagh; Maxted, Nigel; Venanzoni, Roberto; Negri, Valeria
ABSTRACT: The aim of this study was to construct a solid basis for developing a crop wild relatives (CWR) and wild harvested plants (WHP) conservation strategy at the European and national levels. To this end we (i) worked out an annotated and synonymized Working Database of the Italian Vascular Plants, (ii) worked out a full CWR–WHP checklist for Italy, (iii) worked out a prioritized CWR and WHP inventory, (iv) identified native taxa with an ascertained utility for breeding, and (v) on the basis of a gap analysis case study on two Brassica taxa, outlined the first steps to be taken immediately to develop their in situ and ex situ conservation strategy. The Working Database of the Italian Vascular Plants includes a total of 11, 710 taxa. Of those, 92.0% form the CWR–WHP checklist. On the basis of the importance of the related crops, their status, and their need of protection and/or monitoring, 1118 taxa were prioritized. Of these, 129 taxa deserve the highest priority in planning a conservation strategy, including 16 that currently have a practical use in breeding. The case study showed that little is still known about relic CWR populations and that not all of them are adequately protected in situ and ex situ. Since information on their abundance, location, distribution, ecological conditions, census, and current conservation is lacking, initiatives should be put into action immediately for developing a national and European conservation strategy.